A One-Year Economic Evaluation of Six Alternative Strategies for the Management of Uninvestigated Upper Gastrointestinal Symptoms in Canadian Primary Care. (2010) - Barkun, Alan N; Crott, Ralph; Fallone, Carlo A; Kennedy, Wendy A; Lachaine, Jean; Levinton, Carey; Armstrong, David; Chiba, Naoki; Thomson, Alan; van Zanten, Sander Veldhuyzen; Sinclair, Paul; Escobedo, Sergio; et al.
Abstract : BACKGROUND: The cost-effectiveness of initial strategies in managing Canadian patients with uninvestigated upper gastrointestinal symptoms remains controversial. OBJECTIVE: To assess the cost-effectiveness of six management approaches to uninvestigated upper gastrointestinal symptoms in the Canadian setting. METHODS: The present study analyzed data from four randomized trials assessing homogeneous and complementary populations of Canadian patients with uninvestigated upper gastrointestinal symptoms with comparable outcomes. Symptom-free months, quality-adjusted life-years (QALYs) and direct costs in Canadian dollars of two management approaches based on the Canadian Dyspepsia Working Group (CanDys) Clinical Management Tool, and four additional strategies (two empirical antisecretory agents, and two prompt endoscopy) were examined and compared. Prevalence data, probabilities, utilities and costs were included in a Markov model, while sensitivity analysis used Monte Carlo simulations. Incremental cost-effectiveness ratios and cost-effectiveness acceptability curves were determined. RESULTS: Empirical omeprazole cost $226 per QALY ($49 per symptom-free month) per patient. CanDys omeprazole and endoscopy approaches were more effective than empirical omeprazole, but more costly. Alternatives using H2 -receptor antagonists were less effective than those using a proton pump inhibitor. No significant differences were found for most incremental cost-effectiveness ratios. As willingness to pay (WTP) thresholds rose from $226 to $24, 000 per QALY, empirical antisecretory approaches were less likely to be the most cost-effective choice, with CanDys omeprazole progressively becoming a more likely option. For WTP values ranging from $24, 000 to $70, 000 per QALY, the most clinically relevant range, CanDys omeprazole was the most cost-effective strategy (32% to 46% of the time), with prompt endoscopy-proton pump inhibitor favoured at higher WTP values. CONCLUSIONS: Although no strategy was the indisputable cost-effective option, CanDys omeprazole may be the strategy of choice over a clinically relevant range of WTP assumptions in the initial management of Canadian patients with uninvestigated dyspepsia.